PENGARUH RASIO PROFITABILITAS, LEVERAGE, LIKUIDITAS DAN INFLASI TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Pratiwi, Devita; Astawinetu, Erwin Dyah (JEM17: Jurnal Ekonomi Manajemen, 2021)
The purpose of this study was to determine and analyze the effect of Profitability, Leverage, Liquidity and Inflation on Firm Value either partially or simultaneously. The population in this study are all food and beverages sub-sector companies listed on the Indonesia Stock Exchange. The sample used is 12 food and beverages sub-sector companies that meet the criteria. This type of research used quantitative research methods with associative methods. The results of this study partially show that the Profitability (NPM) variable has a significant effect on Firm Value, while the Leverage (DER), Liquidity (CR) and Inflation variables have no significant effect on Firm Value. Simultaneously Profitability (NPM), Leverage (DER), Liquidity (CR) and Inflation have a significant effect on Firm Value.